ANALISIS KECERDASAN INTERPERSONAL SISWA KELAS XI SEKOLAH MENENGAH ATAS ISLAM HARUNIYAH PONTIANAK - Fuadi, Zakiul (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract The study aims to analyze the interpersonal intelligence grade students high school of Islam haruniyah Pontianak. The shape of this research is a survey study. While the sample of this research is a class XI student high school of Islam haruniyah Pontianak. Data collection technique used was indirect communication in the form of multiple choice questionnaire totaling 58 items. to calculate the data using the questionnaire results and analysis techniques as follows percentage X% = x 100%. The formula to determine the range of scores by pophan and sirotnik (in Sari, 2013) as follows: ideal - (Z x s ideal) s / d ideal + (Z x s ideal). Based on the results of data analysis showed that interpersonal intelligence reached 76.44% of students are in the high category. Keywords: Interpersonal Intelligence